2011
DOI: 10.1155/2011/845879
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation after Bacterial Meningitis in Infants Younger Than 9 Months

Abstract: Objective. To describe the audiological, anesthesiological, and surgical key points of cochlear implantation after bacterial meningitis in very young infants. Material and Methods. Between 2005 and 2010, 4 patients received 7 cochlear implants before the age of 9 months (range 4–8 months) because of profound hearing loss after pneumococcal meningitis. Results. Full electrode insertions were achieved in all operated ears. The audiological and linguistic outcome varied considerably, with categories of auditory p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…This is a well-known phenomenon, related with the reduced survival rate of spiral ganglion cells in postmeningitic cochleas. [28][29][30] The personal experience with CIs after long-term deprivation was also quite disappointing: in agreement with the literature [31][32][33], none of our pre-verbal children receiving a CI after 10 years of age ever equalled the speech perception performances of earlier CI recipients (below 3 years of age at surgery).…”
Section: Discussionsupporting
confidence: 83%
“…This is a well-known phenomenon, related with the reduced survival rate of spiral ganglion cells in postmeningitic cochleas. [28][29][30] The personal experience with CIs after long-term deprivation was also quite disappointing: in agreement with the literature [31][32][33], none of our pre-verbal children receiving a CI after 10 years of age ever equalled the speech perception performances of earlier CI recipients (below 3 years of age at surgery).…”
Section: Discussionsupporting
confidence: 83%
“…Finally, fixation of the electrode in the inferior mastoid tip is not advisable as the distance to the round window will increase substantially with temporal bone growth. Taking these considerations into account, which are increasingly important the younger the infant, we did not observe any peri or postoperative complications in these children under 9 months [Roukema et al, 2011].…”
Section: Cochlear Implantation In Young Postmeningitis Patients: Decimentioning
confidence: 60%
“…The specific surgical issues to be taken into consideration for these very young patients are discussed [Roukema et al, 2011].…”
Section: Cochlear Implantation In Young Postmeningitis Patients: Decimentioning
confidence: 99%
See 1 more Smart Citation
“…There is still no evidence that the meningitis causative agent is related to a better or worse prognosis. Additionally, with the analysis of more than 1600 cases of meningitis, it was found that there is no causative agent of meningitis that is more likely to cause LO, although there is a higher risk that Streptococcus pneumoniae meningitis may cause profound hearing loss 22 . Less populated spiral ganglions may be observed in such cases 12 .…”
Section: Discussionmentioning
confidence: 99%